Energising Environmental Sustainability in Sub-Saharan Africa: the role of Governance Quality in Mitigating the Environmental Impact of Energy Poverty - Stephen Kelechi Dimnwobi; Kingsley Ikechukwu Okere; Favour Chidinma Onuoha; Benedict Ikemefuna Uzoechina; Chukwunonso Ekesiobi; Ebele Stella Nwokoye (African Governance and Development Institute (AGDI), 2023)
The Sub-Saharan Africa region is disproportionately affected by energy poverty and is considered highly vulnerable to the impacts of climate change. Therefore, addressing the pressing challenges of energy poverty and promoting environmental sustainability in this region is of paramount importance. Consequently, this study appraises the relationship between energy poverty and ecological preservation in Sub-Saharan Africa from 2005 to 2020, using government effectiveness and regulatory quality as moderating variables. A combination of energy poverty indicators and an index of energy poverty computed via the principal component analysis method were applied to identify the link between energy poverty and ecological sustainability. The instrumental variable generalized method of moment technique was applied to address the likelihood of endogeneity issues, and the Driscoll-Kraay approach was employed to check the consistency of the instrumental variable generalized method of moment method. Key findings indicate that energy poverty expands the ecological footprint in Sub-Saharan Africa, leading to ecological deterioration, while the interaction with government effectiveness and regulatory quality further deteriorates the environment. Subsequently, the study provides several recommendations to mitigate the influence of energy poverty on the environment.
Keywords: 330; Energy Poverty; Environmental Sustainability; Government Effectiveness; Regulatory Quality; Sub-Saharan Africa